EFEKTIVITAS INTERVENSI AQUATIC THERAPY UNTUK MENINGKATKAN BALANCE PADA PENDERITA STROKE : Literature Review - Sekar Hapsari Putri Handayani, (2020)
Stroke is a chronic disease that caused by the brain experiencing a lack of blood supply. A person who has or had a stroke has a reduced ability to balance which contributes to increasing the state of fear of falling. Conditions that are often encountered are walking disorders and balance disorders due to contractures in the ankle plantarflexion. This study aims to conduct a narrative study of existing research as a means of obtaining objective evidence related to the effectiveness of aquatic therapy interventions to improve balance in stroke patients. The method of this research is literature review. The parameter used is the Berg Balance Scale, while for the methodological assessment using The Physiotherapy Evidence Database rating scale (PEDro Scale). Results from 7 Random Controlled Trial or RCT studies were obtained with a total of 141 males and 98 females with 1 sub-acute stroke and 6 chronic stroke studies. The conclusion of a narrative study in studies compiled in this literature review shows that the administration of aquatic therapy interventions can significantly (P <0.05) in increasing balance in stroke patients.